Multilayer dodecahedrons Zn-Co sulfide for supercapacitors. (10th September 2020) - Zhao, Jing; Hou, Shuangyue; Bai, Yongqing; Lian, Yue; Zhou, Qiuping; Ban, Chaolei; Wang, Zhifeng; Zhang, Huaihao
Abstract: Transition metal sulfides have attracted much attention in recent years due to their high theoretical specific capacitance and conductivity. In this work, the two-layer heterogeneous metal sulfides (Zn-Co-S) were prepared successfully using the zinc-cobalt fund organic framework as a sacrificial template. The composite materials were characterized by a variety of means and its performance as electrode material for supercapacitor was also tested in detail. Resultantly, the 2L-ZnCoS (two layers of Zn-Co-S) has good electrochemical properties: its specific capacitance is up to 971.01 C g −1 at the specific current of 1 A g −1 with 90.3% retention after 10, 000 cycles. As for the asymmetric supercapacitor 2L-ZnCoS//AC assembled with 2L-ZnCoS as positive electrode and activated carbon as negative electrode, it showed excellent performance: when the power density was 0.80 kW kg −1 and 8.09 kW kg −1, the energy density were as high as 51.76 Wh kg −1 and 31.63 Wh kg −1 correspondingly. This advanced performance is due to its unique double-layer hollow structure and the synergistic effect, which are helpful to acquire more electrochemical active sites and transport pathways to accelerate ion transport. Accordingly, the well-designed double-layer hollow composite sulfide is an ideal electrode material for high performance supercapacitors.